Design Decisions for a Powertrain Combination of Electric Motor and Propeller for an Electric Aircraft - Ralf Johannes Keuter; Bastian Kirsch; Jens Friedrichs; Bernd Ponick (IEEE Access, 2023)
For the sizing of an electric motor, the diameter and length of the installation space are important parameters that significantly influence and limit the characteristics of the electric motor. From an aerodynamic point of view, it is not technically advantageous to choose a propeller hub diameter that is larger than mechanically necessary. The hub diameter defines the installation space ans thus the outer diameter for the electric motor driving the propeller. The research question that arises is this: Is there an optimum diameter for the hub and thus the electric motor and how is it limited? The present work should help to establish a better understanding of the system combination of electric motor and propeller, especially the choice of the diameter and further geometrical parameters of the electric motor. A parameter study investigating aeromechanical and electromagnetic aspects has been performed and the results are combined to achieve the best solution in terms of efficiency and power density. The investigations show that an increase in the diameter causes little disadvantage from an aerodynamic point of view, but the improvements to the electric motor are significant only up to the point where the diameter-to-length ratio becomes too high and end-region effects become more significant. The installation space for the electric motor could be determined using a hub-to-tip ratio of 0.16 to 0.20, which is applicable to any propeller. In addition, it could be shown that a co-optimisation of the speed throughout a mission profile with regard to the efficiency is affected by the propeller alone.